2020
DOI: 10.1002/advs.202001546
|View full text |Cite
|
Sign up to set email alerts
|

Fluoride‐Free 2D Niobium Carbide MXenes as Stable and Biocompatible Nanoplatforms for Electrochemical Biosensors with Ultrahigh Sensitivity

Abstract: Recently, 2D niobium carbide MXene has drawn vast attention due to its merits of large surface area, good metallic conductivity, and tunable band gap, making it desirable for various applications. However, the usage of highly toxic fluoride-containing etchant and quite long etching time in the conventional synthesis route has greatly hindered further exploration of MXene, especially restricting its biomedical application. Herein, novel fluoride-free Nb 2 CT x nanosheets are prepared by a facile strategy of ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
58
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(66 citation statements)
references
References 44 publications
1
58
0
Order By: Relevance
“…Conventional HF etching synthesis method of MXenes may bring some obstructions for their biosensing applications [62]. For example, due to excessive use of HF acid the F À residues on the surface of MXenes are prone to release HF during the hydrolysis reactions or electrochemical reactions, and the potential toxicity of HF would relatively reduce the enzyme activity or cause a significant damage to the normal cells in vivo.…”
Section: Enzyme-based Biosensorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Conventional HF etching synthesis method of MXenes may bring some obstructions for their biosensing applications [62]. For example, due to excessive use of HF acid the F À residues on the surface of MXenes are prone to release HF during the hydrolysis reactions or electrochemical reactions, and the potential toxicity of HF would relatively reduce the enzyme activity or cause a significant damage to the normal cells in vivo.…”
Section: Enzyme-based Biosensorsmentioning
confidence: 99%
“…Therefore, safe, robust, and fluorine-free synthesis methods for producing stable and biocompatible MXene nanosheets are essentially required. Song, M. et al [62] constructed a fluoride-free Nb 2 C/acetylcholinesterase (AChE)-based biosensor for the detection of phosmet. They synthesized the 2D fluoride-free Nb 2 C MXene nanosheets through an electrochemical etching (E-etching) exfoliation route (Figure 3) and the obtained fluoride-free Nb 2 C showed good chemical stability, low cytotoxicity, high porosity, large surface area and enhanced conductivity which were beneficial to the stabilization of enzyme activity and the promotion of electrochemical activity.…”
Section: Enzyme-based Biosensorsmentioning
confidence: 99%
“…In recent years, 2D niobium carbide (Nb 2 CT x ) MXene has attracted extensive attention because of its large specific surface area, high metal conductivity, adjustable bandgap, and other advantages, and has broad application prospects. Song et al [18] prepared novel fluorine (F)-free Nb 2 CT x nanosheets using simple electrochemical etching and these results showed that the specific surface area of electrochemically etched Nb 2 CT x was 35.3 m 2 g −1 (Figure 5a,b). Based on the rapid aluminum removal, good chemical stability, and biocompatibility of electron-etched MXene, an F-free Nb 2 CT x /acetylcholinesterase biosensor was constructed for the detection of photosensitive compounds.…”
Section: Advantages and Disadvantages Of Mxenes In Biological Fieldsmentioning
confidence: 99%
“…For example, in Nb 2 CT x MXene nanosheets, the Nb atoms located on the surface of the bond with the surrounding oxygen during the exposure process, destroying the stability of the hexagonal structure of Nb 2 C and degrading it. In addition, the initial conductivity of the Ti 3 C 2 T x field-effect transistor decreases by ≈20% following exposure to air for 70 h. [18] Synthesized MXenes are usually stored in an oxygen-free, [31] MXenes with various structures and properties can be prepared using different surface functional groups, greatly enriching the MXene family. The main MXene synthesis method is the MAX phase stripping method, which selectively etches a layer in the MAX phase through high-frequency etching with an etchant, and single or several layers of MXene nanosheets are obtained by ultrasonic treatment or intercalation.…”
Section: Disadvantages Of Mxenesmentioning
confidence: 99%
“…MXenes, which are known as two-dimensional materials, have attracted extensive attention due to their similar structure and analogous performances to graphene. The versatile chemical structure, compositions, and tunable surface functionalization of MXenes facilitate the diverse applications of MXene, such as in solar cells [42], electronic devices [43], catalysts [44,45], gas sensors or biosensors [46,47], and cancer therapy [48]. MXenes have nanosheet-like structure, unique surface chemistry, high conductive properties, and excellent biocompatibility.…”
Section: Introductionmentioning
confidence: 99%